Sustainable recovery and reutilization of cereal processing by-products - Galanakis, Charis Michel (Woodhead Publishing in food science, technology, and nutrition., 2018)
Sustainable Recovery and Reutilization of Cereal Processing By-Products addresses topics associated with the sustainable management of cereal manufacturing. Emphasis is placed on current, advisable practices, general valorization techniques of cereal processing by-products, and the functional properties of healthy cereal by-product components that lead to target applications in foods and nutraceuticals. Focus includes discussions on wheat bran, distillers' dried grains-based within the biorefinery concept, and different techniques for the separation, extraction, recovery and formulation of valuable compounds, including proteins, arabinoxylans, and beta-glucan.